1992
DOI: 10.1152/ajpendo.1992.263.1.e64
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indirect calorimetry and a new breath 13C/12C ratio method during strenuous exercise

Abstract: A new stable isotope method for the determination of substrate oxidation rates in vivo is described and compared with indirect calorimetry at rest and during high-intensity exercise (30 min at 80-85% maximal O2 uptake capacity) in six well-trained cyclists. This method uses the absolute ratios of 13C/12C in expired air, endogenous glucose, fat, and protein in addition to O2 consumption and is independent of CO2 production (VCO2). Carbohydrate and fat oxidation rates at rest, calculated by both methods, were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 14 publications
6
99
0
Order By: Relevance
“…Thus, the increase in RER in these exercise conditions is almost completely explained by the balance between oxidized carbohydrates and lipids, independent of blood lactate. The validity of this calorimetric approach is further confirmed by a classical work of Romijn (Romijn et al, 1992) who showed in highly trained sportsmen that up to 80-85% VO 2 max calorimetric calculations based on respiratory exchanges during exercise closely fit with much more sophisticated measurements using stable isotopes (MacRae et al, 1995). Concerning proteins, if one compares exercise bouts at 33 and 66% of VO 2 max it can be demonstrated that their use for oxidation remains stable at the various levels of exercise, supporting the basal assumption that the balance of substrates may be interpreted in terms of respective percentage of oxidized fat and carbohydrates.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, the increase in RER in these exercise conditions is almost completely explained by the balance between oxidized carbohydrates and lipids, independent of blood lactate. The validity of this calorimetric approach is further confirmed by a classical work of Romijn (Romijn et al, 1992) who showed in highly trained sportsmen that up to 80-85% VO 2 max calorimetric calculations based on respiratory exchanges during exercise closely fit with much more sophisticated measurements using stable isotopes (MacRae et al, 1995). Concerning proteins, if one compares exercise bouts at 33 and 66% of VO 2 max it can be demonstrated that their use for oxidation remains stable at the various levels of exercise, supporting the basal assumption that the balance of substrates may be interpreted in terms of respective percentage of oxidized fat and carbohydrates.…”
mentioning
confidence: 58%
“…Our protocol based on 6-minutes workloads seems preferable (Bordenave et al, 2007). As already developed above, Romijn (Romijn et al, 1992) compared, in highly trained endurance cyclists, calorimetric results and isotopic measurement during exercise tests up to 85% VO 2 max and showed that at this level calorimetry is fully reliable. However, a look at the figures of this paper shows that the steady state of RER occurs after 4 min and is not obtained after 2 minutes.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Oxygen and CO 2 exchange rates were converted to caloric equivalents (Lusk, 1924), according to the assumption of low- to-moderate intensity work load and a respiratory exchange ratio (RER) below the blood CO 2 buffer level (Romijn et al, 1992). Metabolic cost measurements were considered acceptable if the average RER value over the final 2路min of each trial was 0.92 or less.…”
Section: Metabolic Cost Measurementmentioning
confidence: 99%
“…19 In fact, it has been demonstrated that the contribution of bicarbonatederived CO 2 to VCO 2 is rather negligible and that VCO 2 can be considered to be a reliable reflection of muscle tissue CO 2 production during exercise, including at high intensity, as long as RER is lower than 1. 20,21 Furthermore, as previously shown, this type of exercise testing can be used to characterize alterations in substrate utilization in the obese during exercise 6 and has clear beneficial effects. [8][9][10] In this study, the values of W max , expressed in absolute value, in terms of percentage of predetermined W max and in terms of heart rate corresponding to COP ox , were very close to those reported previously in overweight females.…”
Section: Discussionmentioning
confidence: 90%